UJI EFEKTIVITAS SALEP EKSTRAK ETANOL DAUN SIRIH CINA (Peperomia pellucida) TERHADAP PENYEMBUHAN LUKA EKSISI PADA TIKUS PUTIH (Rattus norvegicus) - Rika Puspita Sari (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
ABSTRAK Wahyuni. Test the effectiveness of Chinese betel leaf ethanol extract ointment on excision wound healing in white rats (Supervised by: apt.Rika Puspita Sari, S.farm.,M.Si ) Wounds are physical injuries that can cause tears and damage to skin tissue. One type of the wound is an excision wound. An excision of wound caused by the cutting of tissue by a sharp object. The main goal in wound management is to achieve rapid healing with optimal fuction and good result. That can be achieved by preventing infection and trauma by providing an environtment that optimizes wound healing. One of the plants that have the potential to heal wounds is the Chinese betel plant that have the potential to heal wounds is the Chinese betel plant the purpose of the research to determine the effectiveness of giving Chinese betel leaf extract on excision wound healing in white rats(rattus norvegicus). The research was conducted in the laboratory of health the husada deli tua. The method of the research conducted out experimentally, the sample was extracted by the maceration method. And then the extract was formulated into ointment availability with concentrations of 2%,4%, and 8% furthermore, on evaluation of the availability of the ointment was carried out, by organoleptic test, homogeneity test, pH test and spreadability test. The result of the research for each group gave the best treatment experienced a decrease in the diameter of the cut wound was the positive control group (povidone iodine) and 8% concentration. Conclusions: the ethanol extract of chial betel leaf has the effectiveness of healing excision wounds at a concentration of 8% Keywords: Chinese betel leaf extract, excision wound